Pemanfaatan Serbuk Karet Terhadap Kuat Tekan dan Daya Redam Beton non Struktural - Guntur Nugroho; Restu Faizah; Dhanang Deddy Handoko (Bulletin of Civil Engineering, 2022)
Waste tires are a serious problem in many countries in the world, including Indonesia, this is because waste is a solid material that is difficult to decompose and even recycle. The utilization of waste tires in the field of civil engineering and environmental infrastructure is something that needs to be developed. Utilization of rubber powder can be used as a partial substitute for sand in concrete mixtures used in structural concrete and non-structural concrete. This research was conducted by experimental method on cylindrical specimens to test the compressive strength and concrete blocks to test the damping power of 28 days old concrete. The test parameters are the compressive strength and damping coefficient of the rubber powder mixture. The variation of thetest object used is the replacement of used tire rubber powder against sand by 0%, 5%, 10%, 15%, and 20%. The test results show that the more mixture of rubber powder in the concrete can reduce the compressive strength of the concrete and increase the damping ratio of the concrete.